HIC : Health Immunity Certificate Using NFC Technology for Controlling and Monitoring of COVID - 19 Patient Movement during and after MCO Period - Mohd Kamir, Yusof; Wan Aezwani, Wan Abu Bakar; Mustafa, Man (2020)
Coronavirus disease (Covid-19) is an infectious disease caused by a newly first discovered coronavirus in Wuhan, China. Statistics reveals more than 3 million of total cases with more than 900K recovery and more than 200K deaths around the world as to date. Those recovered Covid-19 patients already have Covid-19 immunity in their body system. Movement Control Order (MCO) is the government enforcement policy during and after lockdown period for controlling the person’s movement from red, yellow and green zone in combating the disease. During MCO period, it is vital to control and monitorthose recovered Covid-19 patient movement so that when they pass each security road blocks, they just show their health immunityid without having further explanation and clarification regarding their current status to the authority party. In response to Covid-19 issues, we propose a Health Immunity Certificate (HIC) with Near Field Communication (NFC) tag that acts as recovered patient’s immunity passports or Patient Identification (PID). This certificate allows those Covid-19 recovered patient to be exempted from any movement restrictions from or to red, yellow or green zone to perform their daily activity. Our HIC offers a high security with 2 way encryption-decryption id. Prior to simulation done, resultsindicate that HIC system is executed at average of 0.001245 seconds of each HIC scans at each particular roadblock. This shows that our proposed HIC may contribute to significant usage to those Covid-19 frontliners such as Majlis Keselamatan Nasional (MKN), security agencies or even medical practitioners.